The woman in white [videorecording (DVD)] - Buckley, Jessie, 1989-; Hardy, Ben, 1991-; Vinall, Olivia; Collins, Wilkie, 1824-1889 (PBS Distribution, 2018)
Tells of a pair of half sisters whose lives end up caught in a grand conspiracy revolving around a mentally ill woman dressed in white. As the story unfolds, murder, love, marriage, and greed stand between the two women and happy lives. Their only hope is the secret the woman in white waits to tell them.